An international survey of MRI qualification and certification frameworks with an emphasis on identifying elements of good practice. Issue 1 (February 2017) - Castillo, J.; Caruana, C.J.; Morgan, P.S.; Westbrook, C.; Mizzi, A.
Abstract: The purpose of the study was to survey MRI qualification and certification frameworks in the major English-speaking countries (Australia, New Zealand, US, Canada, UK, Ireland) with the aim of identifying elements of good practice. The intention is to incorporate these elements in a national framework that could be used in supporting an MRI specialist register. The study was conducted using document analysis of MRI qualification and certification documents from these states with data triangulated through a web-based questionnaire amongst an expert group of MRI radiographers (n = 59) from the same states. Based on the results of the study, recommendations have been put forward for those countries that are in the process of developing such frameworks. The main recommendations include that a professional or regulatory body externally accredits MRI programmes and that learning outcomes be based on an MRI competence profile that addresses current and forecasted needs of the particular country. The MRI competence profile should encompass a novice-to expert continuum and be referenced directly to a national qualification framework. Ideally each level of expertise should be assessed and evidenced by a portfolio of CPD activities, including clinical and management case studies appropriate to that level. Highlights: Professional or regulatory bodies should accredit MRI academic programmes. Competence profiles should reflect and support local MRI services. MRI competence profiles should be structured in a novice-to-expert continuum format. Competence profiles should reference national qualification/certification frameworks. Mandatory certification could lead to registration in an MRI specialist register.